2020
DOI: 10.1002/joc.6599
|View full text |Cite
|
Sign up to set email alerts
|

Arid–humid variations in the summer climate and their influence mechanism in Asian monsoon margin of Northwest China during 1960–2010: A case study in the Alashan Plateau

Abstract: In the Asian monsoon margin of Northwest China, the impact factors for variations in the aridity and humidity of the summer climate are complex and unclear. In this study, we selected the Alashan Plateau, located in the midlatitude arid zone and the Asian monsoon margin of Northwest China, as the study area. Changes in the aridity index K (a proxy for the arid-humid variations in the summer climate of the Alashan Plateau) were calculated for the period 1960-2010 using meteorological data. Relationships among t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(6 citation statements)
references
References 65 publications
0
6
0
Order By: Relevance
“…Located within continental Eurasia, ARNC comprises Xinjiang Province, the Hexi Corridor (Gansu Province), the Qaidam Basin (Qinghai Province), and the Alashan Plateau (Inner Mongolia) (Figure 1). Although mid-latitude westerlies mainly dominate ARNC, the climate of easternmost ARNC is interactively affected by the westerlies and the East Asian summer monsoon (EASM) (Li et al, 2020). Owing to the long distance from oceans, the presence of many high mountain ranges such as (from north to south) the Altai, Tianshan, Qilian, and Kunlun Mountains, and the adjacent Qinghai-Tibet Plateau, moisture flow over ARNC is strongly blocked, resulting in mean annual precipitation amount of <200 mm in ARNC (Chen et al, 2014;Wang Y. et al, 2017).…”
Section: Study Areamentioning
confidence: 99%
See 1 more Smart Citation
“…Located within continental Eurasia, ARNC comprises Xinjiang Province, the Hexi Corridor (Gansu Province), the Qaidam Basin (Qinghai Province), and the Alashan Plateau (Inner Mongolia) (Figure 1). Although mid-latitude westerlies mainly dominate ARNC, the climate of easternmost ARNC is interactively affected by the westerlies and the East Asian summer monsoon (EASM) (Li et al, 2020). Owing to the long distance from oceans, the presence of many high mountain ranges such as (from north to south) the Altai, Tianshan, Qilian, and Kunlun Mountains, and the adjacent Qinghai-Tibet Plateau, moisture flow over ARNC is strongly blocked, resulting in mean annual precipitation amount of <200 mm in ARNC (Chen et al, 2014;Wang Y. et al, 2017).…”
Section: Study Areamentioning
confidence: 99%
“…Further east, extreme precipitation is interacted by the westerlies and the summer monsoon (Li et al, 2015;Du et al, 2020). In summer, blocked by the Tianshan and Altai mountains, EASM provides abundant water vapor and causes precipitation over the eastern Alashan Plateau (Li et al, 2020).…”
Section: Spatial Pattern Of Extreme Precipitation Occurrence Timementioning
confidence: 99%
“…The study area is located in the Asian monsoon margin of NW China (Li et al, 2020a). In this region, precipitation and effective moisture changes at the millennial scale during the Holocene differed from those observed in the typical monsoon region (Li et al, 2015b;Gao et al, 2020aGao et al, , 2020b.…”
Section: Mechanisms Possibly Forcing Climate Changesmentioning
confidence: 99%
“…1), covering an area of 52,100 km 2 with an elevation of 900–1500 m (Zhu et al, 2010). It is characterized by a strong continental climate (Xu and Li, 2016; Li et al, 2020a). In this desert area, the mean annual temperature ranges from 8.8°C to 9°C (Li et al, 2018).…”
Section: Study Areamentioning
confidence: 99%
“…Droughts, especially meteorological droughts, indicate precipitation shortfalls and are usually associated with certain atmospheric circulations (Huang et al., 2016; Li et al., 2020; Zhou et al., 2016). Some studies have demonstrated that the variability in drought in northern China is mainly impacted by the intensity of westerly winds and the East Asian monsoon (Zhang et al., 2007, 2016), and the semiarid zones of China, a large area from northeast to southwest, become wetter (drier) when the East Asian summer monsoon is stronger (weaker) (Zhang et al., 2016).…”
Section: Introductionmentioning
confidence: 99%